An Analysis Compound Words In Taylor Swift’s Song Lyrics - Nainggolan, Erni Susianti; Ismi Adinda (Universitas Cokroaminoto Palopo, 2025)
The research aims to discover the types, word formations, and meanings of compound words which existed in song lyrics by Taylor Swift in 2014. The writers used descriptive qualitative method based on the McCharty theory, in which the writers applied it to determine the number of compound words are found in Taylor Swift’s song lyrics. The method described the findings of the research by describing it systematically with qualitative data analysis. In collecting the data, the writers did some steps: listening to the song lyrics of Taylor Swift, collecting the data of compound words, classifying the compound words into the types and formations, and getting the meanings of the compound words. From the data analysis, there were 17 compound words of 5 song lyrics. From the 17 compound words were classified into 11 compound noun (64,70%), 3 compound adjective (17,64%), and 9 compound verb (17,64%). The result indicated that compound word derived from compound noun was the highest.